In vitro antibacterial activity of ozonized propyleneglycol (Endozone®) on Enterococcus faecalis in root canals of bovine teeth - Alata-Marcavillaca, Andrea Katioska (2018)
Objective: Determine the antibacterial activity in vitro of ozonized Propyleneglycol (Endozone ®) and ultrasound on Enterococcus faecalis (E. faecalis) in root canals of bovine teeth. Methods: The study was experimental, and carried out in the microbiology laboratory of the Faculty of Biology of the Altiplano University. The samples were seeded in bile esculin agar, bovine teeth were contaminated with E. faecalis was carried out, bovine teeth were contaminated with E. faecalis to which was applied Endozone® and ultrasound at different times of action, after this procedure the count of the colony development for each tooth was done using the structured direct observation technique. Results: The average of the antibacterial activity of Endozone® on Enterococcus faecalis was 92%, the average antibacterial activity of Endozone® applied with ultrasound for 10 seconds was 94,63%, applied for 20 seconds was 95,01% and applied for 30 seconds was 96,74%, we observed that the antibacterial activity is directly proportional to the time of application, the statistical test of Kruskall-Wallis indicated that there were significant differences between the different times of application. Conclusions: Endozone® with ultrasound application had a higher antibacterial effect than Endozone® on E. faecalis. The application of Endozone® and ultrasound for 30 seconds showed greater antibacterial activity.